Synergistic effect of potential alpha-amylase inhibitors from Egyptian propolis with acarbose using in silico and in vitro combination analysis - Ahmed A. Nada; Aly M. Metwally; Aya M. Asaad; Ismail Celik; Reham S. Ibrahim; Safa M. Shams Eldin (BMC, 2024)
Abstract Background Type 2 Diabetes mellitus (DM) is an affliction impacting the quality of life of millions of people worldwide. An approach used in the management of Type 2 DM involves the use of the carbohydrate-hydrolyzing enzyme inhibitor, acarbose. Although acarbose has long been the go-to drug in this key approach, it has become apparent that its side effects negatively impact patient adherence and subsequently, therapeutic outcomes. Similar to acarbose in its mechanism of action, bee propolis, a unique natural adhesive biomass consisting of biologically active metabolites, has been found to have antidiabetic potential through its inhibition of α-amylase. To minimize the need for ultimately novel agents while simultaneously aiming to decrease the side effects of acarbose and enhance its efficacy, combination drug therapy has become a promising pharmacotherapeutic strategy and a focal point of this study. Methods Computer-aided molecular docking and molecular dynamics (MD) simulations accompanied by in vitro testing were used to mine novel, pharmacologically active chemical entities from Egyptian propolis to combat Type 2 DM. Glide docking was utilized for a structure-based virtual screening of the largest in-house library of Egyptian propolis metabolites gathered from literature, in addition to GC-MS analysis of the propolis sample under investigation. Thereafter, combination analysis by means of fixed-ratio combinations of acarbose with propolis and the top chosen propolis-derived phytoligand was implemented. Results Aucubin, identified for the first time in propolis worldwide and kaempferol were the most promising virtual hits. Subsequent in vitro α-amylase inhibitory assay demonstrated the ability of these hits to significantly inhibit the enzyme in a dose-dependent manner with an IC50 of 2.37 ± 0.02 mM and 4.84 ± 0.14 mM, respectively. The binary combination of acarbose with each of propolis and kaempferol displayed maximal synergy at lower effect levels. Molecular docking and MD simulations revealed a cooperative binding mode between kaempferol and acarbose within the active site. Conclusion The suggested strategy seems imperative to ensure a steady supply of new therapeutic entities sourced from Egyptian propolis to regress the development of DM. Further pharmacological in vivo investigations are required to confirm the potent antidiabetic potential of the studied combination.